Performa ikan hias rainbow kurumoi (Melanotaenia parva Allen, 1990) dengan pemberian maggot [Performance of ornamental fish Lake Kurumoi rainbowfish (Melanotaenia parva Allen, 1990) fed using maggot] - Yogi Himawan; I Wayan Subamia (Jurnal Iktiologi Indonesia, 2013)
Kurumoi rainbowfish (Melanotaenia parva Allen, 1990) is an Indonesian ornamental fish which has quite attractive color. The objective of eksperiment is to determine the performance of rainbow kurumoi fed using maggot. Treatment design used completely randomized design (CRD), in the form of feeding: A (pellet), B (maggot), and C (maggot fish silage). Each treatment was repeated three times. Rainbow Kurumoi that used have an average weight of 9.1±0.1 g and standard length of an average of 3.5±0.02 cm, maintained solids tocking 10 fish per container in containers measuring length x width x height is 50 cm x 40 cm x 30 cm and filled with water as much as ±20 L with a stagnant system for 21 days. Feeding as much as 10% of the biomass was given twice a day. The results showed that the highest growth achieved in treatment C with final weights and average length of raw 15.23±0.5 g and 5.2±1.0 cm. Survival rate of each treatment had similar results which amounted to100%. Water quality parameters during the maintenance period are still in the normal range. Abstrak Ikan hias rainbow kurumoi (Melanotaenia parva Allen, 1990) merupakan spesies asli Indonesia yang memiliki warna cukup menarik. Tujuan penelitian ini adalah untuk menganalisis performa ikan hias rainbow kurumoi yang diberi pa-kan maggot. Perlakuan menggunakan Rancangan Acak Lengkap (RAL), berupa pemberian pakan: A (pelet), B (maggot), dan C (maggot silase ikan). Tiap perlakuan diulang tiga kali. Ikan rainbow kurumoi dengan bobot rata-rata 9,1±0,1 gram dan panjang baku rata-rata 3,5±0,02 cm, dipelihara dengan padat tebar 10 ekor per wadah dalam wadah berukuran panjang x lebar x tinggi adalah 50 cm x 40 cm x 30 cm dan diisi air sebanyak ± 20 L dengan sistem stagnan selama 21 hari. Pemberian pakan sebanyak 10% dari biomassa dua kali setiap hari. Hasil penelitian menunjukkan bahwa pertum-buhan tertinggi dicapai pada perlakuan C dengan bobot akhir dan panjang baku rata-rata 15,23±0,5 gram dan 5,2±1,0 cm. Sintasan tiap perlakuan memiliki hasil yang sama yakni sebesar 100%. Parameter kualitas air selama masa pemeliharaan masih berada pada kisaran normal.